Implementing enhanced recovery after bariatric surgery protocol: a retrospective study - Proczko, Monika (J Anesth, 2015)
While the demand for bariatric surgery is increasing, hospital capacity remains limited. The ERABS (Enhanced Recovery After Bariatric Surgery) protocol has been implemented in a number of bariatric centers. We retrospectively compared the operating room logistics and postoperative complications between pre-ERABS and ERABS periods in an academic hospital. The primary endpoint was the length of stay in hospital. The secondary endpoints were turnover times—the time required for preparing the operating room for the next case, induction time (from induction of anesthesia until a patient is ready for surgery), surgical time (duration of surgery), procedure time (duration of stay in the operating room), and the incidence of re-admissions, re-operations and complications during admission and within 30 days after surgery. Of a total of 374 patients, 228 and 146 received surgery following the pre-ERABS and ERABS protocols, respectively. The length of hospital stay was significantly shortened from 3.7 (95 % confidence interval [CI] 3.1–4.7) days to 2.1 (95 % CI 1.6–2.6) days (P < 0.001). Procedure (surgical) times were shortened by 15 (7) min and 12 (5) min for gastric bypass and gastric sleeve surgery, respectively (P < 0.001 for both), by introducing the ERABS protocol. Induction times were reduced from 15.2 (95 % CI 14.3–16.1) min to 12.5 (95 % CI 11.7–13.3) min (P < 0.001).Turnover times were shortened significantly from 38 (95 % CI 44–32) min to 11 (95 % CI 8–14) min. The incidence of re-operations, re-admissions and complications did not change.